Incubation of neural alcohol cue reactivity after withdrawal and its blockade by naltrexone. (12th February 2019) - Bach, Patrick; Weil, Georg; Pompili, Enrico; Hoffmann, Sabine; Hermann, Derik; Vollstädt‐Klein, Sabine; Mann, Karl; Perez‐Ramirez, Ursula; Moratal, David; Canals, Santiago; Dursun, Serdar M.; Greenshaw, Andrew J.; et al.
Abstract: During the first weeks of abstinence, alcohol craving in patients may increase or "incubate." We hypothesize that Naltrexone (NTX) blocks this incubation effect. Here, we compared NTX effects on neural alcohol cue reactivity (CR) over the first weeks of abstinence and on long‐term clinical outcomes to standard treatment. Male alcohol‐dependent patients ( n  = 55) and healthy controls ( n  = 35) were enrolled. Participants underwent baseline psychometric testing and functional magnetic resonance imaging (fMRI) assessment of mesolimbic alcohol CR. Patients participated in a standard treatment program with the option of adjuvant NTX. They received another scan after 2 weeks of treatment. We found higher CR in several brain regions in patients versus healthy controls. CR significantly increased over 2 weeks in the standard treatment group ( n  = 13) but not in the NTX group ( n  = 22). NTX significantly attenuated CR in the left putamen and reduced relapse risk to heavy drinking within 3 months of treatment. Additionally, increased CR in the left putamen and its course over time predicted both NTX response and relapse risk. Carrier status for the functional OPRM1 variant rs1799971:A > G was considered but had no effect on NTX efficacy. In conclusion, NTX was most effective in patients with high CR in the left putamen. While the results from our naturalistic study await further confirmation from prospective randomized trials, they support a potential role of neural CR as a biomarker in the development of precision medicine approaches with NTX. Abstract : After baseline assessment, alcohol dependent patients (N = 55) were offered either naltrexone (NTX) or standard psychosocial therapy (SPT). After 2 weeks of treatment, the patients receiving SPT (N = 13) showed a significant increase in cue reactivity (CR) in the putamen that was associated with an increased relapse risk, while NTX blocked increases in left putamen CR and reduced relapse risk. Especially, the group with increased baseline putamen CR responded favorably to NTX treatment.